A COMPREHENSIVE APPROACH TO THE DIAGNOSIS OF MISCARRIAGE IN THE FIRST TRIMESTER - Gulnara D. Matrizaeva (Central Asian Journal of Medicine, 2024)
Miscarriage is a pressing issue in modern medicine. Clinical, morphological and immunohistochemical features of the endometrium structure may be the basis of this pathology, which is why it is very important to study its features and structure in healthy women and women with reproductive losses of reproductive age. And only on the basis of these parameters can we prove a change from the norm and understand the cause of miscarriage from a clinical and pathomorphological point of view.